Physiological demands of young women's competitive gymnastic routines - Marina, M.; Rodriguez, F. A. (Biology of Sport, 2014)
The objective of this study was to investigate the physiological indices of competitive routines in women`s artistic gymnastics by characterizing post-exercise heart rate (HR), oxygen uptake (VO2) and peak blood lactate concentration (Lmax) in a group of eight young elite-oriented female gymnasts. HR was continuously monitored with Polar RS400 monitors during the test event simulating a competition environment. Within 5 s of the end of each routine, the breath-by-breath gas analyser mask was placed on the face to record VO2. VO2max was calculated by the backward extrapolation method of the VO2 recovery curve. Lmax was obtained during recovery (min 1, 3, 5, 7 and 10) subsequent to each event. One week later, HR, VO2 and Lmax were measured during an incremental continuous treadmill test. The treadmill test was confirmed as the assessment with the highest physiological demand. The gymnasts reached their highest values of HR (183-199 beats · min- 1), VO2/Bm (33-44 ml · kg-1 · min-1) and Lmax (7-9 mmol · l-1) in the floor and uneven bars exercises. The vault was the event with the lowest HR (154-166 beats · min-1) and Lmax (2.4-2.6 mmol · l-1), and the balance beam had the lowest VO2 (27-35 ml · kg-1 · min-1). The mean relative peak intensities attained in the different events, which ranged from 65 to 85% of the individual VO2max and HRmax recorded in the laboratory, suggest that cardiorespiratory and metabolic demands are higher than previously indicated. The high percentage of VO2 measured, particularly after the floor event, suggests that aerobic power training should not be neglected in women`s artistic gymnastics.